The ABC's of Human Survival: A Paradigm for Global Citizenship - Arthur Clark (Global Peace Studies, 2010)
The ABCs of Human Survival examines the effect of militant nationalism and the lawlessness of powerful states on the well-being of individuals and local communities-and the essential role of global citizenship within that dynamic. Based on the analysis of world events, Dr. Arthur Clark presents militant nationalism as a pathological pattern of thinking that threatens our security, while emphasizing effective democracy and international law as indispensable frameworks for human protection. Within the contexts of history, sociology, philosophy, and spirituality, The ABCs of Human Survival calls into question the assumptions of consumer culture and offers, as an alternative, strategies to improve overall well-being through the important choices we make as individuals.